Ab-initio study of the beryllium-sulphur and beryllium-nitrogen co-doped graphene for nanoelectronic and optoelectronic devices - Manyala, Ncholu I. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.